Pengaruh Brand Engagement Terhadap Brand Awareness dan Brand Image Serta Dampaknya Terhadap Brand Equity Pada PT. Kimia Farma Tbk Medan - Sasabilah, Fahira; Nasution, Aulia Arief; Pentana, Sopi (Cattleya Darmaya Fortuna, 2024)
This study aims to determine the effect of brand engagement on brand awareness and brand image partially. To determine the effect of brand engagement, brand awareness and brand image on brand equity partially. To determine the effect of brand engagement on brand equity through brand awareness and brand image at PT. Kimia Farma Tbk Medan. The population in this study was 100 and all of them were sampled using the saturated sampling technique. The analysis technique used is path analysis. The results showed that brand engagement had a positive and significant effect on brand awareness, brand engagement had a positive and significant effect on brand image, brand engagement had no effect on brand equity, brand awareness had a positive and significant effect on brand equity, brand image had a positive and significant effect on brand equity, there is no effect of brand engagement on brand awareness and its impact on brand equity and there is no effect of brand engagement on brand image and its impact on brand equity.